ECONOMIC AND DEMOGRAPHIC DETERMINANTS OF CRIME INCIDENCE IN INDIA - Abish. j; Elpinston, DR.G. Gnana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The society has been hampered by crime in many ways in recent days. Particularly, economic and property crimes have emerged due to the economic imbalances and population density in the country. The total economic and property crime in India has been on the rise. Therefore, it is necessary to study the macro-economic and demographic factors that impact the crime rate. The main purpose of this paper is to investigate the relationship between a few macro-economic (GDP, GDP per capita, and inflation) and demographic (population) factors with the IPC (Indian Penal Code), economic and property crimes in India, as well as their impact. The data has been collected from the National Crime Records Bureau (NCRB), the World Bank, and the United Nations Population Prospects. The Pearson correlation and simple regression were the tools used to determine the relationship and impact between selected macro variables and economic and property crimes. The results of the study found that in most cases there was a significant positive relationship between crime and GDP, GDP per capita, and population, and a significant negative correlation was found between crime and inflation in India. The positive correlation between GDP, GDP Per Capita and crimes makes it evident that there is a larger unequal economic distribution exists in India. The government should focus more on the schemes to decrease income inequality and rich-poor gap rather than spend money unnecessarily on those that only boost GDP and GDP per capita.